Cation-exchanged Al-substituted ETAS-10 for adsorption of CO2 and N2 - Birje, Amit R.; Yadav, Tushar R.; Nandanwar, Sachin U. (Industrial & Engineering Chemistry Research, 2026)
In this study, Al-substituted ETAS-10 was synthesized via a seed-assisted hydrothermal method by varying the Al:Ti molar ratio. The material was modified via ion exchange with Li+, Ca2+, K+, and Sr2+ cations to tailor its adsorption behavior. The structural, morphological, and textural properties of the synthesized adsorbents were characterized by using XRD, FE-SEM, HR-TEM, EDS, Raman spectroscopy, CO2-TPD, and N2 physisorption. Li+-ETAS-10 exhibited a higher surface area and stronger basic sites available for the CO2 adsorption compared to the studied samples. The equilibrium adsorption isotherms of CO2 and N2 were measured at 25 degrees C and pressures up to 20 bar. Among the studied samples, ETAS-10 with an Al/Ti ratio of 0.2 showed the highest CO2 uptake of 3.19 mmol/g at 20 bar. This performance was enhanced by Li+ cation exchange, which increased the CO2 capacity to 3.52 mmol/g due to improved microporosity and stronger electrostatic interactions between CO2 molecules and the small radii of the Li+ cation. The adsorption isotherms follow the Langmuir model, indicating that adsorption behavior aligns with Langmuir assumptions across the investigated pressure range. Overall, the results highlight the synergistic role of framework Al incorporation and targeted cation exchange in enhancing the CO2 adsorption performance of ETAS-10. These materials exhibit potential as adsorbents for capture/adsorption of CO2.